2010
DOI: 10.1016/j.jpubeco.2009.11.001
|View full text |Cite
|
Sign up to set email alerts
|

The rate of return to the HighScope Perry Preschool Program

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
597
3
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 971 publications
(654 citation statements)
references
References 25 publications
13
597
3
9
Order By: Relevance
“…A common practice to add, say, 50 cents for every dollar spent on a public project to account for tax distortions, but completely ignoring the distributional benefits of tax instruments at the same time, is incorrect, see for example Heckman et al (2010). Such practice is bound to yield policy errors, because many public projects can now fail the social cost-benefit test, whereas they could be socially desirable.…”
Section: Social Cost-benefit Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A common practice to add, say, 50 cents for every dollar spent on a public project to account for tax distortions, but completely ignoring the distributional benefits of tax instruments at the same time, is incorrect, see for example Heckman et al (2010). Such practice is bound to yield policy errors, because many public projects can now fail the social cost-benefit test, whereas they could be socially desirable.…”
Section: Social Cost-benefit Analysismentioning
confidence: 99%
“…As a result, public projects are less likely to pass a cost-benefit test. For example, Heckman et al (2010) evaluate the Perry Preschool Program and add 50 cents per dollar spent to account for the deadweight costs of taxation. Many other examples can be given, but the message is clear: The marginal cost of public funds has a tremendous impact on how governments should evaluate the desirability of public policies.…”
Section: Introductionmentioning
confidence: 99%
“…A growing literature documents that developmental experiences during a child's first few years are critical to establishing the foundation for achievement throughout life [12]. This period is especially important for children receiving CCDF subsidies, since most of them come from disadvantaged families and face a gap in preparedness for school and educational achievement relative to their peers.…”
Section: World Of Labormentioning
confidence: 99%
“…In long-term panels, young children with better language, cognitive, motor, and socio-emotional development have better outcomes in adulthood (Case and Paxson 2008;Currie and Thomas 2001;Moffitt et al 2011). Plausibly exogenous improvements in maternal education (Carneiro et al 2013), early nutrition (Hoddinott et al 2008;Maluccio et al 2009), the quality of the home environment (Eckenrode et al 2010;Gertler et al 2014;Olds et al 1998), preschool attendance (Berlinski et al 2008;Campbell et al 2002Campbell et al , 2014Heckman et al 2010), and kindergarten classroom quality (Chetty et al 2011) have been shown to result in higher school achievement, better health status, lower levels of criminal behavior, and better labor market outcomes in developed and developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly apparent in small-scale pilots of model programs like the Perry Preschool Program in Ypsilanti, Michigan (Heckman et al 2010;Schweinhart et al 2005) and the Abecedarian Program in Chapel Hill, North Carolina (Campbell et al 2002(Campbell et al , 2014. There is also evidence of benefits from Head Start, the nationwide program which reaches almost one million lowincome children in the United States.…”
Section: Introductionmentioning
confidence: 99%